Neuropsychological factors related to progression of subjective cognitive decline: Neuropsychology/Early detection of cognitive decline with neuropsychological tests. (7th December 2020) - Ryoo, Nayoung; Suh, Jeewon; Son, Eunji; Pyun, Jung Min; Park, Young Ho; Kim, SangYun
Abstract: Background: Individual with subjective cognitive decline (SCD) complains of cognitive decline on its own while cognitively normal. Current research suggests that SCD can indicate an at‐risk stage of Alzheimer's disease (AD). In this study, we analyzed neuropsychological factors in SCD patients at a higher risk of progression to MCI. Method: This retrospective cohort study included 68 patients who were confirmed with SCD after neuropsychological test. They were classified into progressive SCD group and stable SCD group according to whether they progressed to MCI within the follow‐up period. For both groups, neuropsychological tests including Seoul verbal language test, Boston naming test, Stroop color & word test, Rey complex figure test, and forward and backward digit span test were assessed. Result: We collected neuropsychological data of 107 SCD individuals retrospectively, and 68 patients were followed up for a mean of 52.93 months (range 11–113 months). At follow‐up, 35.3% of patients showed cognitive decline to a diagnosis of mild cognitive impairment (MCI) and defined as progressive SCD group (N=24), and the other patients (N=44) were as stable SCD group. Patients with progressive SCD were about 4 years older and more likely to have ischemic heart disease. Furthermore, they showed worse performance on a delayed recall and a recognition task from the Seoul Verbal Learning Test, and Boston naming test compared to those with stable SCD. Conclusion: SCD patients with progression of MCI have a tendency of older age, higher rate of ischemic heart disease, and worse decline in memory and language ability. This study suggest that it is worth to consider SCD subtypes based on memory and language ability so that it is possible to detect a high‐risk group of MCI at the early stage.